Exploring the Distinctive American Aboriginal Culture in Louis Erdrich's The Antelope Wife - Ramesh Prasad Adhikary, PhD (University of Chitral Journal of Linguistics and Literature, 2022)
The objective of this study is to investigate and analyze the various cultural aspects of Native Americans in Louis Erdrich's novel The Antelope Wife. This research also aims to examine how the novel challenges the marginalization of Native American culture by mainstream Western culture. The novel is analyzed using a qualitative approach through close reading and interpretation of the text. Native American thinkers such as Gerard Vizenor, George Elias, and Anna Secco provide theoretical insights that support the analysis. The research finds that The Antelope Wife portrays the complexity and plurality of Native American culture caused by different customs, languages, rituals, and religions. The novel highlights the valorization of Native American culture through the lifestyle, clothing, behavior, attitudes, and values of protagonist Scranton Roy and other Native American characters. The research also shows how the novel challenges the relative marginalization of Native American culture by mainstream Western culture by foregrounding Native American culture. Due to its rich and nuanced representation of Native American society, the study concludes that The Antelope Wife is an important contribution to Native American literature. The novel challenges the marginalization of Native American culture by mainstream Western culture by highlighting the richness and diversity of Native American culture. The research emphasizes the importance of recognizing and valuing diverse cultures and calls for greater respect and appreciation for Native American culture.